Methyltransferase like 21C interaction with Hsc70 affects chicken myoblast differentiation - Jia Cheng; Ruiqing Li; Ling Wang; Tao Zhang; Guoqiang Yuan; Hongzhao Lu (Italian Journal of Animal Science, 2023)
Skeletal muscle has an essential role in boiler production, which depends on the muscle fibre development during the embryonic stage. Whereas the posttranslational modifications of both histone and non-histone proteins are known to regulate postnatal muscle development, the biological significance of non-histone methylation is poorly understood. Recently, the methyltransferase like 21 C (METTL21C) is identified as a non-histone lysine methyltransferase whose role in chicken muscle function remains elusive. In this study, METTL21C was found by comparing free-range and caged modes in Lueyang black-boned chicken aged 60 and 120 days. Quantitative real-time PCR (qPCR) analysis demonstrated that METTL21C was mainly enriched in chicken soleus (SOL) and gastrocnemius muscle (GA) (p < .05). Meanwhile, METTL21C had a rapid increase during chicken myoblast differentiation. After METTL21C overexpression, myogenic differentiation (MyoD) and myogenin (MyoG) expression were significantly increased, indicating that METTL21C promotes chicken myoblast differentiation. Using co-immunoprecipitation (Co-IP) and liquid chromatography-mass spectrometry (LC-MS/MS) analysis, heat shock cognate 71 kDa protein (Hsc70) was confirmed to interact with METTL21C, while the effects of Hsc70 Lys-561 (Hsc70 K561) mutation suggested that Hsc70 was a METTL21C target protein. These results identify the molecular mechanism of METTL21C interaction with Hsc70 associated with chicken myoblast differentiation in the postnatal period.Highlights The mRNA of methyltransferase like 21C (METTL21C) was significantly increased in free-rang mode and during the chicken myoblast differentiation. Overexpression of METTL21C promoted the primary chicken myoblasts proliferation and differentiation. METTL21C could mediate the lysine methylation modification of heat shock cognate 71 kDa protein (Hsc70) to regulate the proliferation of chicken myoblasts.